Spirituality at Workplace: A Brief Literature Review - Lianto Lianto (Journal of Social Research, 2023)
This essay aims to present a concise literature review for spirituality at workplace or what is also commonly called workplace spirituality. This theme is very interesting these days but it is still rare to find a literature review. To assist researchers and academics in their research, this concise literature review can be a reference. In this short article, researchers obtain a study of the grand theory, definition, dimensions, and significance of workplace spirituality.